EDUCATION IN GLOBAL INFORMATION-COMMUNICATION AND ANTHROPOGENIC ENVIRONMENT: NEW OPPORTUNITIES AND LIMITS - Sergey F. Sergeev (Открытое образование (Москва))
The article answers the question of how to use global anthropogenic environments in order to create effective educational environment. We demonstrate both technological and didactic abilities and limits of modern environment-based technologies, and provide a new approach to the educational environment creation.